Chondrogenesis of human bone marrow mesenchymal stromal cells in highly porous alginate-foams supplemented with chondroitin sulfate - Huang, Zhao; Nooeaid, Patcharakamon; Kohl, Benjamin; Roether, Judith; Schubert, Dirk W.; Meier, Carola; Boccaccini, Aldo R.; Godkin, Owen; Ertel, Wolfgang; Arens, Stephan; Schulze-Tanzil, Gundula (Materials Science and Engineering C, 2015)
To overcome the limited intrinsic cartilage repair, autologous chondrocyte or bone-marrow-derived mesenchymal stromal cell (BM-MSC) was implanted into cartilage defects. For this purpose suitable biocompatible scaffolds are needed to provide cell retention, chondrogenesis and initial mechanical stability. The present study should indicate whether a recently developed highly porous alginate (Alg) foam scaffold supplemented with chondroitin sulfate (CS) allows the attachment, survival and chondrogenesis of BM-MSCs and articular chondrocytes. The foams were prepared using a freeze-drying method; some of them were supplemented with CS and subsequently characterized for porosity, biodegradation and mechanical profile. BM-MSCs were cultured for 1-2 weeks on the scaffold either under chondrogenic or maintenance conditions. Cell vitality assays, histology, glycosaminoglycan (sGAG) assay, and type II and I collagen immunolabelings were performed to monitor cell growth and extracellular matrix (ECM) synthesis in the scaffolds. Scaffolds had a high porosity similar to 93-95% with a mean pore sizes of 237 +/- 48 mu m (Alg) and 197 +/- 61 mu m (Alg/CS). Incorporation of CS increased mechanical strength of the foams providing gradually CS release over 7 days. Most of the cells survived in the scaffolds. BM-MSCs and articular chondrocytes formed rounded clusters within the scaffold pores. The BM-MSCs, irrespective of whether cultured under non/chondrogenic conditions and chondrocytes produced an ECM containing sGAGs, and types II and I collagen. Total collagen and sGAG contents were higher in differentiated BM-MSC cultures supplemented with CS than in CS-free foams after 14 days. The cell cluster formation induced by the scaffolds might stimulate chondrogenesis via initial intense cell-cell contacts. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Chondrogenesis; Alginate-foam scaffolds; Chondrocytes; Mesenchymal stromal cells; Chondroitin sulfate